An Accent-Based Approach to Automatic Rendering of Piano Performance: Preliminary Auditory Evaluation - BISESI, Erica; PARNCUTT, Richard (Archives of Acoustics, 2011)
We are exploring the relationship between accents and expression in piano performance. Accents are local events that attract a listener’s attention and are either evident from the score (immanent) or added by the performer (performed). Immanent accents are associated with grouping (phrasing), metre, melody and harmony. In piano music, performed accents involve changes in timing, dynamics, articulation, and pedalling; they vary in amplitude, form, and duration. We analyzed the first eight bars of Chopin Prelude op. 28 n. 6. In a separate study, music theorists had marked grouping, melodic and harmonic accents on the score and estimated the importance (salience) of each. Here, we mathematically modeled timing and dynamics in the prelude in two ways using Director Musices (DM) – a software package for automatic rendering of expressive performance. The first rendering focused on phrasing following existing and tested procedures in DM. The second focused on accents – timing and dynamics in the vicinity of the accents identified by the theorists. In an informal listening test, 10 out of 12 participants (5 of 6 musicians and 5 of 6 non-musicians) preferred the accent-based formulation, and several stated that it had more variation of timing and dynamics from one phrase to the next.